Peningkatan Hasil Pembelajaran Mahasiswa melalui Pembuatan Video dalam Mata Kuliah Umum Bahasa Indonesia di UPN Veteran Surabaya - Siti Umi Hanik; Yunita Suryani; Rika Istianingrum (Universitas Muhammadiyah Jember, 2024)
This research aims to analyze the effect of making video tutorials on increasing students' understanding of material in the General Indonesian Language Course, especially in the material on Citation Writing and Using the Mendeley Application at the National Development University (UPN) Veteran Surabaya. Multimedia-based learning, especially video, is expected to improve students' understanding of the material, skills in using the Mendeley application, as well as their ability to speak in front of the camera (public speaking). This research uses a Classroom Action Research (PTK) approach which involves two cycles, namely the application of making video tutorials and continuous improvement. The research subjects consisted of 50 students who took this course in the odd semester of the 2023-2024 academic year. The research results showed a significant increase in understanding of the material, ability to use Mendeley, and students' confidence in speaking in front of the camera after they made video tutorials. Apart from that, video-based learning also encourages the use of social media and digital applications in the learning context, in accordance with the characteristics of generation Z who are familiar with digital technology. In conclusion, video-based learning methods can improve student learning outcomes in a more active, creative and interactive way, in line with the increasingly profound advances in digital technology in the current era.